Green Environmentally Sustainable Flipped Classrooms Using Social Networks - Martínez-Puma, Elena Guillermina; Rivera-Mansilla, Elmer Benito; Lanchipa-Ale, Alberto Patricio; Ramos-Quispe, Teresa; Villalba-Condori, Klinge Orlando (International Journal of Psychosocial Rehabilitation, 2019)
The objective of this study is to implement the model of flipped classrooms through the use of social networks to improve the attendance and academic performance of master students in management of virtual environments for learning (600 UCSM Scholarship) in the province of Mariscal Nieto, Moquegua region. To this end, a non-experimental cross-sectional design study was carried out. In addition, the study was explanatory, the sample was composed by 55 students from the Master’s Scholarship 600, who were interviewed using a closedquestion interview guide as an application tool. The results show that 25 students (45.45%) responded that they "always" accessed the virtual classroom through social networks to interact with class sessions; 31 students (56.36%) responded that they "strongly agree" that to produce monographs is easier when the teacher relies on audiovisual resources such as the virtual classroom; 20 students (36.36%) responded that they consider this method of inverted classroom project as "strongly didactic"; and finally 26 students (45.45%) responded that the use and management of flip classrooms allowed them to improve their attendance